Toward Critical Electrode/Electrolyte Interfaces in Rechargeable Batteries - Yan, Chong; Xu, Rui; Xiao, Ye; Ding, Jun‐Fan; Xu, Lei; Li, Bo‐Quan; Huang, Jia‐Qi (Advanced functional materials, 2020)
The electrode/electrolyte interface plays a critical role in stabilizing the cycling performance and prolonging the service life of rechargeable batteries to meet the sustainable energy requirements of the mobile society. The understanding of interfaces is still at the preliminary stage due to the limited research techniques and variable properties with time and potential. Herein, the latest developments focused on the interfaces in rechargeable systems including the cathode electrolyte interphase (CEI) and solid electrolyte interphase (SEI) are reviewed. The possible formation mechanisms of the electrode/electrolyte interface are discussed, followed by the introduction of two key influencing factors, specific adsorption and solvated coordinate structure, which will dominate the formation of the interface. Finally, the structure and chemical composition of the interface as well as the possible transport mechanism of lithium ions in the interface and the strategies to regulate the pathway through the interface are presented in detail. This work sheds light on the fundamental understanding of the interface and provides rational scientific principles in designing the electrode/electrolyte interface and inspires the rational design of long‐term cycling rechargeable batteries. The electrode/electrolyte interface plays a critical role in stabilizing the cycling performance and prolonging the service life of rechargeable batteries. This work discusses the formation mechanism of the interface and summarizes the progress in the structure/composition modulation of the interface toward advanced battery systems.